Occupational Toxicity and Health Hazards of the Healthcare Providers at Healthcare Facilities in Sulaimani City, Iraq - Aziz, Tavga Ahmed; Hama Amin, Renas Raouf; Ahmed, Zheen Aorahman; Jalal Sleman, Hazhan; Hassan Aziz, Bahez (Iraqi Journal of Pharmaceutical Sciences, 2021)
Objective: The present study aimed to evaluate the occupational health hazards that face health care providers in Sulaimani City.Methods: A cross-sectional study conducted utilizing quantitative data collection methods. It involved 159 respondents including Physicians, Pharmacists, Medical assistants, Laboratory Instructors and Nurses who worked in 8 major health facilities in Sulaimani city, Kurdistan region, Iraq.Results: Nurses were the most susceptible group to sharp related injuries 13.84%, cuts and wounds 10.69% than the others and they were more experiencing verbal abuse in the workplace 15%. Laboratory instructors represent the most exposed group to contaminated specimens/biohazards 17.6% and blood borne pathogens 13.84, while the physicians represent the most prone group to acquire infectious diseases 15.1% and both the physicians and the nurses were equally exposed to airborne diseases 11.32%. Furthermore, physicians were the most group that suffered from work related stress 13.8%; and medical assistants were the most susceptible to radiation 3.1%. Meanwhile, Laboratory instructors were the most exposed group to physical distress 15.1%, falls 5%, unsafe staffing 13.8%, chemical spills 8.8% and noise 5.4%.Conclusion: Healthcare providers in these settings experienced various types of occupational hazards in their workplaces, which became a dominant issue among the health care providers. Interventions should be established to alleviate these hazards.